2018
DOI: 10.1007/s00127-018-1557-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence rates, reporting, and psychosocial correlates of stalking victimization: results from a three-sample cross-sectional study

Abstract: Behavioral approaches to epidemiological and criminal justice stalking victimization are recommended. Victimization under reporting to healthcare and legal professionals were observed. Further research and prevention programming is needed to capitalize on data concerning personality and coping skills, sexual diversity, and trauma-related psychiatric symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
1
17
2
2
Order By: Relevance
“…The model of comorbidity is supported by the data in the present study too. Cannabis use, cyberbullying victimization and total victimization are associated with an increased risk of being stalking victims, consistent with the previous findings ( Fisher et al, 2002 ; Nobles et al, 2018 ; Reyns et al, 2016 ; Reyns and Scherer, 2018 ). The weak effect of the cannabis use warrants further examination.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The model of comorbidity is supported by the data in the present study too. Cannabis use, cyberbullying victimization and total victimization are associated with an increased risk of being stalking victims, consistent with the previous findings ( Fisher et al, 2002 ; Nobles et al, 2018 ; Reyns et al, 2016 ; Reyns and Scherer, 2018 ). The weak effect of the cannabis use warrants further examination.…”
Section: Discussionsupporting
confidence: 91%
“…What is interesting is the effect of mental health on stalking victimization. Previous studies allude a positive association ( Johnson and Thompson, 2016 ; McEwan et al, 2017 ; Noble et al, 2018 ) while we have found a negative correlation. That is, in the present study, those who self-rate themselves better in mental health condition are less likely to be a stalking victim.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…To measure depression and anxiety symptoms, the shortened Beck Depression Inventory (BDI) [35,36] and the State-Trait Anxiety Inventory (STAI) [37,38], respectively, were used. The shortened version of the BDI consists of 13 items [39] that permit the classification of symptoms and attributes according to a level of gravity: none or minimal depression (scores 0-4), mild depression (5-7), moderate depression (8)(9)(10)(11)(12)(13)(14)(15), or severe depression (>15) (in this study, Cronbach's α was 0.82). The State-Trait Anxiety Inventory consists of two forms (STAIY1 and STAIY2; 20 items each) used to assess how participants feel "right now", at this moment, and how they feel most of the time (respectively, for state anxiety and trait anxiety).…”
Section: Methodsmentioning
confidence: 90%
“…Due to the nature of the motives for using the Internet and social networks (e.g., searching for new friends) [7], young people are more likely to become victims of cyberstalking than other violent and repetitive phenomena. The victimization seems to decrease with age, while the likelihood of reporting stalking victimization tends to increase [8]. For example, findings from Spitzberg and Hoobler's [1] investigation showed that almost one-third of 235 undergraduate college students reported some form of unwanted online pursuit.…”
Section: Introductionmentioning
confidence: 99%